2010
DOI: 10.1073/pnas.1013798107
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of ionic conductances contributes to diverse symptoms of demyelination

Abstract: Fast axonal conduction of action potentials in mammals relies on myelin insulation. Demyelination can cause slowed, blocked, desynchronized, or paradoxically excessive spiking that underlies the symptoms observed in demyelination diseases. The diversity and timing of such symptoms are poorly understood, often intermittent, and uncorrelated with disease progress. We modeled the effects of demyelination (and secondary remodeling) on intrinsic axonal excitability using Hodgkin-Huxley and reduced Morris-Lecar mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…This includes aspects of AP propagation, such as a deeper study of unstable saltatory behaviors in damaged myelinated axons (Boucher et al 2012) or in demyelinated axon (Waxman and Brill 1978;Coggan et al 2010) and their relation to mechanical loading.…”
Section: Future Workmentioning
confidence: 99%
“…This includes aspects of AP propagation, such as a deeper study of unstable saltatory behaviors in damaged myelinated axons (Boucher et al 2012) or in demyelinated axon (Waxman and Brill 1978;Coggan et al 2010) and their relation to mechanical loading.…”
Section: Future Workmentioning
confidence: 99%
“…The internodes nonetheless allowed for the longitudinal spread of both ions and current. Parameter values, ion densities and distributions (soma: g Na = 80, g K = 790, g L = 3, g NaP = 0.19; node or neuroma: g Na = 1500, g K = 1600, g L = 70, g NaP = 1.9, all in mS/cm 2 ) were the same as previously reported (Coggan et al 2010), except when otherwise indicated.…”
Section: Methodsmentioning
confidence: 76%
“…Our HH model (previously described in (Coggan et al 2010, 2011) included a soma (15 µm), axon hillock (8 µm, with 4:1 mm taper), initial segment (10 µm), and a linear set of 80 pairs of myelinated internodes (200 µm each) and nodes of Ranvier (1 µm each). Results were not qualitatively altered by including a T-junction and central axon branch to the end of the initial segment so as to more accurately capture primary afferent morphology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations